Water Hyacinth, an Invasive Species in Africa: A Literature Review - Sharon Indasi Lubembe; Okoth, Sharon; Turyasingura, Benson; Oyugi,Timothy; Ibarasa, Hillary; Moenga, Kelvin; Tumushabe, Jennifer Turyatemba; Chavula, Petros (East African Journal of Environment and Natural Resources, 2023)
Water hyacinth is without a doubt the water invader that causes the most harm to water bodies. Water hyacinths originated from Eastern Mediterranean, West Asia, and Central Asia; they are cultivated and loved worldwide. According to reports, water hyacinth has anti-inflammatory, antifungal, and antibacterial properties. The plant extracts can also be used to treat cholera, sore throats, and snake bites, as well as to scent hair. Water hyacinth Pontederia crassipes (Eichhornia crassipes) has proliferated rapidly in African inland waters, posing numerous threats to fisheries by reducing the existence of some species; water quality by lowering levels of dissolved oxygen; human health and the environment by introducing various disease-causing pathogens and harbouring dangerous animals. The hyacinths further impact human activities by blocking waterways for fishing and destroying habitat for some fish to bread properly. Tourism and navigation are also affected by limiting access to recreational areas, especially for boat cruising. Fishing; effects on fishing activities and effect on plankton production, which is the main food. Different control methods have been utilised and others suggested in Africa, although it has not been fully controlled as it is highly reproductive and still a menace in African inland waters. The most commonly used control measures are biological and physical controls. As a recommendation, all methods should be used in water bodies to reduce its spread as quickly as possible although with caution on chemical methods. In relation to water hyacinth and its effects on terrestrial animals, there is still a need for much research to still be done; however, it is an aquatic plant that is not wanted in many places does not mean it should be eradicated. Its use to produce biogas could be helpful in reducing the challenges that come with it